Students' Creative Thinking Skills in Solving Linear Equation Problems through Contextual Teaching and Learning - Ani Retno Sari; Kana Hidayati (Universitas Syiah Kuala, 2024)
Creative thinking skills are among those that need to be developed in 21st-century learning. Students' creative thinking skills can be improved through CTL, which provides opportunities to explore the relationship between mathematics and the real world. This research aims to determine the application of CTL to enhance students' creative thinking skills in solving linear equation problems. This research used a mixed-methods approach with a sequential explanatory design. The study was conducted with a class of seventh-grade students at a middle school in Yogyakarta. The research subjects consisted of 32 seventh- grade students. The research results show a difference in students' average creative thinking skills in solving linear equation problems before and after implementing CTL. Students' creative thinking skills in the high and medium categories meet the indicators. Meanwhile, students with low creative thinking skills still need help creating mathematical models and solving problems. Further research is required to explore how CTL can be focused on improving the creative thinking skills of students with low levels of ability.